Simultaneous Determination of Drotaverine Hydrochloride and Mefenamic Acid by Isocratic RP-HPLC Method - Ankam, R.; Mukkanti, K.; Durgaprasad, S.; Naidu, P.V.L. (Asian Journal of Chemistry, 2010)
A simple fast, accurate, precise and cost effective isocratic RP-HPLC method is developed for simultaneous determination of drotaverine hydrochloride and mefenamic acid. The retention times of drotaverine hydrochloride and mefenamic acid were found to be 3.05 and 9.52 min, respectively. The method was linear over the range of 16 to 47 ppm with r2 = 0.9999 for drotaverine hydrochloride and 100 to 300 ppm with r2 = 0.9999 for mefenamic acid. Mean recovery for drotaverine hydrochloride and mefenamic acid were 101.1 and 101.2, respectively.